Second Five Year Plan Orissa Progress of Expenditure - Planning Commission (Planning Commission, 1959)
Second Five-Year Plan Summary Statement of State Plan Schemes Groupwise Abstract Statement of State Plan Schemes List of Schemes Proposed to be Financed Out of Miscellaneous Development Loan in 1959-60 Name of the Ministries of Government of India and the Subjects With Which They Are Concerned Heads of Development and Groups In Which Schemes Are Arranged Centrally Sponsored Schemes.
Government of Orissa